Evaluation of alternative powders for Forensic Papilloscopy - Gomes Ferreira, Rafaela; Akemi Okuma, Adriana; Machado Costa, Luciana (Revista Brasileira de Criminalística, 2023)
Fingerprints and other ridge skin impressions has been one of the most important evidences for identifying individuals during a criminal investigation. However, the substances used for fingerprint and other ridge skin impressions revelation in Forensic Papilloscopy are usually toxic. Thus, this work aimed to reduce the risk to which professionals in the area are exposed, through the use of efficient, less toxic and economically viable revealers. Furthermore, the studies were directed to the visualization of latent fingerprints and other ridge skin impressions deposited on different materials with non-porous surfaces such as rough Formica, varnished wood, raw metal, galvanized metal and glass, in order to find more appropriate developers that provide good image resolution in spite of the surface. For this study, a search was made in the literature for non-toxic dyeing substances appropriate for fingerprint and other ridge skin impressions development by the powder method, in addition to a UV-Vis spectrophotometry characterization of its dye compounds. In this context, this work presents the study of the potential for implementation of the food dyes and natural products powders red beet, hibiscus, algae Spirulina, indigo carmine and tartrazine in criminal investigations.